Ecopedagogical Capacity Building to Strengthen the Environmentally Caring Character of Youth in Mendalo Indah Village Through Environment Literacy Classes - Hendra; Salman Jufri; Salman Hasani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
Environmental problems, including waste, are a continuing issue facing the community. The community service activity was motivated by the fact that many residents still litter, visible trash on the streets, and the lack of trash disposal sites on village streets. The community service activity aims to increase the understanding and skills of youth from the Karang Taruna of Mendalo Indah Village in preserving the environment by providing capacity-building training through environmental literacy classes and encouraging concrete actions to protect the environment. The activity was carried out through planning, implementation, and evaluation stages. The results of the community service were the implementation of ecopedagogical capacity-building activities through environmental literacy classes and concrete actions to clean the environment. The training results from the pre-test and post-test showed that 80% of participants understood the religious, socio-cultural, and social environments. In addition, the concrete action activity was attended by youth from Mendalo Indah Village with a cleaning point at the Valencia Housing Complex. The objectives of this activity are to develop and strengthen the environmental care character of youth from Mendalo Indah Village, so that in the future, there will be many programs to maintain the village environment free from waste.